2017
DOI: 10.1021/jacs.7b10245
|View full text |Cite
|
Sign up to set email alerts
|

Tilted, Uninterrupted, Monomeric HIV-1 gp41 Transmembrane Helix from Residual Dipolar Couplings

Abstract: Cryo-electron microscopy and X-ray crystallography have shown that the pre- and post-fusion states of the HIV-1 gp41 viral coat protein, although very different from one another, each adopt C3 symmetric structures. A stable homotrimeric structure for the transmembrane domain (TM) also was modeled and supported by experimental data. For a C3 symmetric structure, alignment in an anisotropic medium must be axially symmetric, with the unique axis of the alignment tensor coinciding with the C3 axis. However, NMR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 32 publications
7
76
0
Order By: Relevance
“…Influenza hemagglutinin was shown to have similar TMD dynamics with tilted and straight orientations, suggesting that these could be common type I viral fusion proteins TMD topologies (Benton et al, 2018). The arrangement of helices shown here for HIV Env is different than the three-helix bundle topology observed in NMR structures of the TM helices alone (Chen and Chou, 2017;Chiliveri et al, 2018;Dev et al, 2016;Hollingsworth et al, 2018;Kwon et al, 2018a). Thus, the compact three-helix bundle conformation likely represents the low-energy post-fusion conformation of the TMD and its formation is preferred in the minimal constructs used in the NMR and MD studies.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Influenza hemagglutinin was shown to have similar TMD dynamics with tilted and straight orientations, suggesting that these could be common type I viral fusion proteins TMD topologies (Benton et al, 2018). The arrangement of helices shown here for HIV Env is different than the three-helix bundle topology observed in NMR structures of the TM helices alone (Chen and Chou, 2017;Chiliveri et al, 2018;Dev et al, 2016;Hollingsworth et al, 2018;Kwon et al, 2018a). Thus, the compact three-helix bundle conformation likely represents the low-energy post-fusion conformation of the TMD and its formation is preferred in the minimal constructs used in the NMR and MD studies.…”
Section: Discussionmentioning
confidence: 64%
“…Structural intermediates have been captured after receptor binding and in complex with antibodies, which illustrate the intricately coordinated structural transitions of Env (Lu et al, 2019;Ozorowski et al, 2017;Tran et al, 2012). This flexibility is compounded when parts below the ectodomain are included, so structures of MPER, TMD and CTD have only been resolved in isolation using NMR (Chiliveri et al, 2018;Dev et al, 2016;Kwon et al, 2018a;Sun et al, 2008). In these studies, the MPER is found as a membrane-embedded amphipathic helix and trimeric protrusion from the membrane, TMD as a three-helix bundle or separate tilted helix, and the CTD as an elongated set of three amphipathic helices, leaving open questions as to how these conformations relate to the full Env trimer assembly.…”
Section: Introductionmentioning
confidence: 99%
“…The highly conserved gp41 TMD transmembrane domain (TMD) of Env ( Figure 1) is anchored in a cholesterol-rich lipid bilayer (22) that is flanked by the membrane proximal external region (MPER) on the exofacial leaflet and the cytoplasmic tail (CT) on the cytofacial leaflet. In the prefusion state, either one (23) or three (21,24,25) single-pass α-helices span the membrane ( Figure 1A). Previous studies have proposed that either oligomeric contacts (21,24) or head group snorkeling (23) stabilizes an internal arginine, R696, which is buried in the membrane (21).…”
Section: Introductionmentioning
confidence: 99%
“…In the prefusion state, either one (23) or three (21,24,25) single-pass α-helices span the membrane ( Figure 1A). Previous studies have proposed that either oligomeric contacts (21,24) or head group snorkeling (23) stabilizes an internal arginine, R696, which is buried in the membrane (21). Additionally, studies purport that a GxxxG motif in the TMD either stabilizes the trimer interface or acts as a signaling domain (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Dai et al [30] showed that a gp41 peptide corresponding only to the MPER-TM region is monomeric in DPC, consistent with our results. More recently, a TM peptide construct, similar to the one used in [31], gave NMR residual dipolar couplings which were inconsistent with a symmetric trimeric structure of the TM but more consistent with a monomeric oligomerization state of the TM [32]. FRET data indicate that the proximity of the TM domains changes in a concentration-dependent manner in DPC micelle (membrane mimic) and are not fixed in a trimeric state.…”
Section: Trimerization Is Energetically Driven By the Ectodomain Onlymentioning
confidence: 99%